Effect of nitrogen and weed control on growth and yield of Java citronella (Cymbopogon winterianus Jowitt) - SINGH, K SINGH, V P SINGH, D V (Journal of Spices and Aromatic Crops, 1998)
Field experiements conducted at Lucknow, India on Java citronella (Cymbopogon winterianus) to study the effect of manual weeding (weed-free condition) and diuron spray (1.5 kg ai/ha) over weedy check (no weeding) alone and also in association with different levels of nitrogen on growth and yield revealed that fresh herbage yeild in weedfree and diuron treated plots were 30 and 15 % more over unweeded plots, respectively, Growth and yield parameters in weed-free and weedy plots significantly increased with increase in nitrogen up to 200 kg N/ha and up to 150 kg N/ha in diuron treated plots, The response equation showed that optimum nitrogen doses in first harvest year were 222,22, 168,18 and 126,32 in weed-free, weedy and Diuron treated plots, respectively; in second harvest year the respective values were 176,67, 158,33 and 106.45, The net return at optimum level of nitrogen was maximum (Rs, 20,065) in weed-free plots followed by diuron (Rs, 18,120) treated plots in first harvest year, whereas in second harvest year, the respective values were Rs, 26,279 and Rs, 25,088, Weed-free plots produced maximum growth and herbage yield followed by diuron treated plots.